The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/em.22000
|View full text |Cite
|
Sign up to set email alerts
|

Bhas 42 cell transformation activity of cigarette smoke condensate is modulated by selenium and arsenic

Abstract: Cigarette smoking remains a major health risk worldwide. Development of newer tobacco products requires the use of quantitative toxicological assays. Recently, v-Ha-ras transfected BALB/c3T3 (Bhas 42) cell transformation assay was established that simulates the two-stage animal tumorigenesis model and measures tumor initiating and promoting activities of chemicals. The present study was performed to assess the feasibility of using this Bhas 42 cell transformation assay to determine the initiation and promotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Conversely, we have shown that the particulate matter (ACM) from e‐cigarettes is negative in the Bhas 42 CTA when tested at concentrations up to 120 µg/mL (77 ng/mL nicotine). This study follows our own previous findings that the Bhas 42 CTA can distinguish between the potential promotion activity of a conventional cigarette and a tobacco heating product [Breheny et al, ], and supports the work of others who demonstrated the potential use of the assay in tobacco product assessment [Weisensee et al, ; Han et al, ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Conversely, we have shown that the particulate matter (ACM) from e‐cigarettes is negative in the Bhas 42 CTA when tested at concentrations up to 120 µg/mL (77 ng/mL nicotine). This study follows our own previous findings that the Bhas 42 CTA can distinguish between the potential promotion activity of a conventional cigarette and a tobacco heating product [Breheny et al, ], and supports the work of others who demonstrated the potential use of the assay in tobacco product assessment [Weisensee et al, ; Han et al, ].…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, this assay has undergone a number of international validation studies and is now the subject of an OCED guidance document [Organisation for Economic and Cooperative Development, ]. Weisensee et al [] and Han et al [] have shown that Bhas 42 CTA could be useful in assessing the promoter activity of complex mixtures such as cigarette smoke. Their work showed that total particulate matter (TPM) from a reference cigarette induced cell transformation in a concentration‐dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…It introduces DNA damage [ 40 – 43 ]. It also induces human and mammalian cell transformation [ 44 46 ] and tumor formation when applied to mouse skin [ 47 49 ]. While it is well established that cigarette smoke introduces a variety of different types of DNA damage, it is less clear how smoke exposure influences DNA repair efficiency and DNA damage response pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Although the Bhas 42 CTA was validated using single chemicals (Sakai et al, 2011), the test method is technically applicable to mixtures and has been used to investigate the transforming effects of cigarette smoke condensate (Weisensee et al, 2013;Han et al, 2016) and PM extracts (Ohmori et al, 2013). Indeed, the original source of Bhas 42 cells, BALB/c A31-1-1, can sustain the metabolism of PAH to carcinogenic intermediates (Kakunaga and Crow, 1980;Lo and Kakunaga, 1982).…”
Section: Introductionmentioning
confidence: 99%